Conceptual framework for a digital organization - Meike Schröder; Sonja Pahlevan (Adapting to the Future: How Digitalization Shapes Sustainable Logistics and Resilient Supply Chain Management. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 31, 2021)
Purpose: Innovative technologies are forcing companies to incorporate digitization more into their value creation processes in order to remain competitive long-term. A transformation to a digital organization is therefore required. Aim of the paper is to identify which key components should be covered during the transformation to a digital organization and should therefore be part of a conceptual framework. The conceptual framework will help companies achieving a holistic transformation into a digital organization. Methodology: Based on an analysis of the literature, the key components necessary to successfully transition to digital organization are identified. The relevance of these core topics are then examined with the help of expert interviews. Based on the results, a conceptual framework for a holistic transformation into a digital organization is developed. Findings: Six key components are identified for the framework, which represent the basic requirements for the transformation into the digital organization. Furthermore, drivers as well as challenges are shown that companies have to overcome in the digital transformation. Originality: Scientifically sound concepts that include a holistic approach to transformation into a digital organization have, until now, lacked the scientific methods used to collect the content. The development of our framework has a scientifically grounding.
urn:nbn:de:gbv:830-882.0162017; hdl:10419/249608; https://econpapers.repec.org/RePEc:zbw:hiclpr:31
Keywords: 650; Innovation management; technology management